2016
DOI: 10.1111/jomf.12301
|View full text |Cite
|
Sign up to set email alerts
|

Does Couples' Communication Predict Marital Satisfaction, or Does Marital Satisfaction Predict Communication?

Abstract: The quality of communication between spouses is widely assumed to affect their subsequent judgments of relationship satisfaction, yet this assumption is rarely tested against the alternative prediction that communication is merely a consequence of spouses’ prior levels of satisfaction. To evaluate these perspectives, newlywed couples’ positivity, negativity, and effectiveness were observed four times at 9-month intervals and these behaviors were examined in relation to corresponding self-reports of relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
155
4
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(189 citation statements)
references
References 37 publications
15
155
4
6
Order By: Relevance
“…First, despite the use of a reasonably sized sample of ethnically diverse couples, larger samples are necessary, as are samples of differing ages and relationship types in order to assess whether the RC construct is broadly applicable. Second, the effect sizes in this study were relatively small, particularly compared to effect sizes observed in the associations between behavior and marital satisfaction (Karney & Bradbury, ; although see Lavner et al, for evidence of modest associations). These small effect sizes may be due to the generally high level of satisfaction in our sample as indicated by the means and standard deviations in Table , as well as the significant skew (skewness men's satisfaction = −1.64, skewness women's satisfaction = −1.59, CSI range = 27–81 for both men and women), which may have constrained the association between satisfaction and other variables.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…First, despite the use of a reasonably sized sample of ethnically diverse couples, larger samples are necessary, as are samples of differing ages and relationship types in order to assess whether the RC construct is broadly applicable. Second, the effect sizes in this study were relatively small, particularly compared to effect sizes observed in the associations between behavior and marital satisfaction (Karney & Bradbury, ; although see Lavner et al, for evidence of modest associations). These small effect sizes may be due to the generally high level of satisfaction in our sample as indicated by the means and standard deviations in Table , as well as the significant skew (skewness men's satisfaction = −1.64, skewness women's satisfaction = −1.59, CSI range = 27–81 for both men and women), which may have constrained the association between satisfaction and other variables.…”
Section: Discussioncontrasting
confidence: 54%
“…In addition, satisfaction has been documented as a consistent predictor of relationship stability (Karney & Bradbury, ; Le, Dove, Agnew, Korn, & Mutso, ), suggesting its importance for relationship outcomes. Observable relationship behavior, including problem‐solving behavior, has been consistently associated with relationship satisfaction for married couples (Eldridge & Christensen, ; Karney & Bradbury, ; Lavner, Karney, & Bradbury, ). Therefore, we expected more competent RC behavior to be associated with greater relationship satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Two same‐sex couples were excluded from analyses because the small sample size precluded comparisons with this group. The percentage of participating families from the initial screening group (18.2%) compares favorably to participation rates in other samples of low‐income couples (e.g., 11.4% in Lavner et al, ), and the percentage of families meeting eligibility criteria who participated in the intervention (46.0%) is comparable to participation rates among eligible families in other trials of relationship education targeting select demographics (e.g., 47.6% among military couples in Stanley et al, ).…”
Section: Methodsmentioning
confidence: 57%
“…Specifically, previous studies have yielded results that confirm (Beach et al, ), provide null results (Williamson et al, ), or even contradict (Schilling, Baucom, Burnett, Allen, & Ragland, ) the hypothesis that gains in dimensions of couple communication predict improved relationship quality in CRE programs. A recent longitudinal study of low‐income newlyweds found that communication positivity, negativity, and effectiveness rarely predicted changes in satisfaction, further challenging the central role of communication for relationship quality (Lavner et al, ). Moreover, results from this study indicated relationship satisfaction more commonly predicted changes in communication, thereby introducing the possibility that relationship satisfaction may be a mechanism for change in communication.…”
Section: Recent Origins Of the Controversymentioning
confidence: 99%
See 1 more Smart Citation